2008
DOI: 10.1186/2046-0481-61-7-455
|View full text |Cite
|
Sign up to set email alerts
|

Trends in cow numbers and culling rate in the Irish cattle population, 2003 to 2006

Abstract: Cows are the main economic production units of Ireland's cattle industry. Therefore, demographic information, including overall numbers and survival rates, are relevant to the Irish agricultural industry. However, few data are available on the demographics of cows within a national population, either in Ireland or elsewhere, despite the recent development of comprehensive national cattle databases in many EU Member States. This study has sought: to determine the rate of cow culling from the national herd; to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 10 publications
1
23
3
Order By: Relevance
“…The levels of age-stratified cattle mortality are comparable to previous reports (Roy, 1990;Gardner et al, 1990;Karuppanan et al, 1997;Gulliksen et al, 2009;Thomsen et al, 2004Ortiz-Pelaez et al, 2008;McConnel et al, 2008;Maher et al, 2008;Perrin et al, 2010;Dechow and Goodling, 2008;Dechow et al, 2011;among others). For example, dairy cow mortality risks of 0.02-0.035 in Denmark 1990-1999(Thomsen et al, 2004), 0.048 in North America 2002(McConnel et al, 2008, mortality rates of 0.051-0.066 in Sweden 2002(Alvasen et al, 2012 have been reported.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The levels of age-stratified cattle mortality are comparable to previous reports (Roy, 1990;Gardner et al, 1990;Karuppanan et al, 1997;Gulliksen et al, 2009;Thomsen et al, 2004Ortiz-Pelaez et al, 2008;McConnel et al, 2008;Maher et al, 2008;Perrin et al, 2010;Dechow and Goodling, 2008;Dechow et al, 2011;among others). For example, dairy cow mortality risks of 0.02-0.035 in Denmark 1990-1999(Thomsen et al, 2004), 0.048 in North America 2002(McConnel et al, 2008, mortality rates of 0.051-0.066 in Sweden 2002(Alvasen et al, 2012 have been reported.…”
Section: Discussionsupporting
confidence: 89%
“…However, despite the existence of comprehensive cattle databases in many countries, representative overviews over mortality rates within a cattle population of a country or region are few. This is both in contrast to the reported need for cattle demographic data and to public concerns regarding farm animal welfare Maher et al, 2008;von Keyserlingk et al, 2009;EFSA, 2009EFSA, , 2011EFSA, , 2012.…”
Section: Discussioncontrasting
confidence: 77%
“…Mortality has been steadily increasing during the last 2 decades all over the world [1]. The mortality rate increased from 2.6 to 5.7% in the United States from 1996 to 2007 [2], and in Ireland from 3.3 to 4.4% between 2002 and 2006 [3]. Shaikh [4] conducted a study on morbidity and mortality in cattle covering four regions of Maharashtra and reported that the overall morbidity and mortality rate in cattle was 19.22% & 12.48%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Involuntary culling is an important reason for the relatively short longevity in highyielding cattle herds, the average being less than three. In high-yielding cattle herds, estimated annual culling rates were between 23% for the total Irish dairy cattle population (Maher et al, 2008) and on average 32% in 2054 'Dairy Herd Improvement' herds (Pinedo et al, 2010). In an experimental herd, culling rates were 25% (Bell et al, 2010).…”
Section: Mixed Rain-fed Systemsmentioning
confidence: 99%
“…In an experimental herd, culling rates were 25% (Bell et al, 2010). In the survey of Maher et al (2008), 35% of cows were culled before their fourth lactation. In the experimental herd (Bell et al, 2010), 58% of cows were culled before their fourth lactation and in this study 68% of culling occurred involuntarily.…”
Section: Mixed Rain-fed Systemsmentioning
confidence: 99%